SPECIAL MEMORY FOR ADDITION TO PROCESS EMULATION IBM PC / XT - Nico Bramanti; Ir. Irwan Nirmara, MM (Jurnal Sistem Komputer, 1998)
To avoid errors charging program into the EPROM emulator created a device as a temporary substitute for the position of the EPROM emulator. This tool serves as a pilot program before it is loaded into the EPROM emulator. Because this type of equipment, including types of memory devices, then to occupy the memory address of the IBM PC / XT had to be recognized and this address is not used by other memory devices. To berkomnukasi with the IBM PC system required interfacing and programming language that can be directly translated by the IBM PC system.